Análisis sobre la rentabilidad de la producción y comercialización de la codorniz en la región Costa del Ecuador - Lindao Vera, Edinson Edilver (2023)
The production and marketing of quail meat and eggs have gained acceptance worldwide due to their protein content and nutritional benefits. However, in the Ecuadorian context, coturniculture is developed in various regions of the country. But before embarking on a quail venture, it is necessary to carry out studies to determine the viability of starting a venture focused on this species. Through this, the profitability of quail production and marketing in the Coastal region of Ecuador must be analyzed, so that they help generate opportunities for the development of poultry ventures. In this work, issues related to the production and marketing of quail will be addressed. With the help of reliable data collection and analysis, it is expected to offer a complete overview of the profitability of quail production and marketing in the Coastal region of Ecuador. Although, for adequate quail production it is necessary to provide a suitable environment, that is, in a clean, safe and well-ventilated place. Quail production presents an encouraging outlook, with estimated costs of US$760.5 to raise 100 quail for the first 6 months. However, the success and profitability of this production depends on several factors, such as market demand, production costs, farm management and product quality, so to thrive in this poultry sector, producers must focus on cost control and ensure compliance with regulations, which requires commitment and rigorous management by the producer; therefore, producer knowledge and commitment is needed to ensure good profitability and thus obtain an excellent result.